Rinorea calcicola (Violaceae), an endangered new species from south-eastern Gabon - van Velzen, Robin; Wieringa, Jan J. (Phytotaxa, 2014)
Rinorea calcicola, endemic to south-eastern Gabon, is described as a new species. Its most striking characteristic is the laminate fruit, a character so far only known for R. zenkeri. Rinorea calcicola has a limited distribution and appears to be restricted to limestone outcroppings. We have assessed it as endangered—EN B1ab(ii,iii,iv,v)—according to IUCN criteria. Morphological affinities of R. calcicola are discussed, and a key to R. zenkeri and the Gabonese species of Rinorea with textured fruits is given. The new species is one of many endemic species from the same region, and we recommend that a study of their distribution and ecology is undertaken to inform conservation planning. Because of the presence of so many narrow endemic species in the region, we suggest that the area be considered for protected status.